Pengoptimalisasian Pencahayaan Buatan pada Kamar Tidur (Studi Kasus: Kamar Kos D’Paris Putri) - Tantya Galuh Puspa Hendika; Chely Novia Bramiana (Jurnal Sipil dan Arsitektur, 2024)
Humans need light to see things directly. The light occurs because of the reflection produced by objects so that the eyes can see clearly and comfortably. The lighting system in a room plays a vital role in creating good lighting quality. It takes a mature design to adjust the lighting according to Indonesian national standards in the room. Excessive light can interfere with the eye's activity to adapt to the surrounding environment. However, insufficient lighting can also hinder the activities of the room's occupants because the eye's ability to recognize the climate decreases, and the visual comfort of the room's occupants is disrupted. Visual comfort can be met if the visual comfort factors are realized optimally, one of which is the regularity of the standard light design regulated in the Indonesian National Standard (SNI) and the room's arrangement to suit the lighting distribution. If natural lighting is not possible in a room, artificial lighting must be optimized. In boarding room number 24 D'paris Kos Putri, there is no natural light entering, so artificial light is needed to support the activities of its occupants and make them more optimal. This study aims to identify whether artificial lighting meets the room lighting standards and optimize it to comply with Indonesian National Standards.